2016
DOI: 10.7314/apjcp.2016.17.4.1865
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Deaminase - a Novel Diagnostic and Prognostic Biomarker for Oral Squamous Cell Carcinoma

Abstract: Background: The number of patients with oral cancer in India is increasing gradually (especially in younger people). Although the diagnostic modalities and therapeutic management of oral cancer are improving, the treatment outcome and prognosis of oral cancer remain poor. The absence of definite early warning symptoms for most head and neck cancers suggests that sensitive and specific biomarkers are likely to be important in screening for high-risk patients. Aims: To analyze serum adenosine deaminase (ADA) lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 7 publications
3
27
0
Order By: Relevance
“…ADA might be increased in an attempt to maintain the clearance of the high levels of adenosine produced by a persistent inflammatory microenvironment and the increased activity of ecto‐nucleotidases . Several studies have shown the clinical use of ADA levels as a diagnostic and/or prognostic marker in various diseases with an important inflammatory component such as oral squamous cell carcinoma, chronic lymphocytic leukemia, tuberculosis, common chronic ears, nose and throat infections, Chagas disease, and leishmaniasis . The great difference in ADA levels between ovarian endometriomas and simple cysts found here suggests that ADA can also be a good biomarker for endometriosis.…”
Section: Discussionmentioning
confidence: 74%
“…ADA might be increased in an attempt to maintain the clearance of the high levels of adenosine produced by a persistent inflammatory microenvironment and the increased activity of ecto‐nucleotidases . Several studies have shown the clinical use of ADA levels as a diagnostic and/or prognostic marker in various diseases with an important inflammatory component such as oral squamous cell carcinoma, chronic lymphocytic leukemia, tuberculosis, common chronic ears, nose and throat infections, Chagas disease, and leishmaniasis . The great difference in ADA levels between ovarian endometriomas and simple cysts found here suggests that ADA can also be a good biomarker for endometriosis.…”
Section: Discussionmentioning
confidence: 74%
“…Also serum ADA levels increased significantly with the histopathological grade. They suggested that serum ADA levels in squamous cell carcinoma of tongue and oral cavity carcinoma might be a useful diagnostic and prognostic biomarkers in clinical practice [16,17]. In contrast Saracoglu et al [19] found that ADA was significantly lower in saliva of the patients with oral cavity cancer compared with larynx cancer patients and control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…ADA enzyme activities in head and neck cancer tissues have presented controversial results in literature review [15][16][17][18][19]. Altered purine metabolism in various cancer types which is affected actively by genetic alterations may be one of the reasons for this discrepancy [20].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies, higher pre‐operative lipoprotein (α) (≥300 mg/L) and lower direct bilirubin (<4.0 μM) were found to be associated with adverse survival time. Recent studies have revealed that serum or salivary ADA levels might be useful in the follow‐up and diagnosis of head and neck carcinomas, which was only based on increased serum ADA levels in OSCC groups as compared to those in healthy individuals. No long‐term survival statistics or large sample sizes were detected, making the results immature.…”
Section: Discussionmentioning
confidence: 99%
“…For example, higher GGT or ALP levels have been demonstrated to predict poor overall survival (OS) or disease‐free survival (DFS) in patients with colorectal, cervical, breast, endometrial, and esophageal cancers . Moreover, patients with malignant tumors, such as ovarian or oral cavity cancer, had higher serum ADA levels compared to normal controls and there were significant differences between the histopathological grade and ADA levels . Therefore, it seems that liver enzymes activities have a negative effect on prognosis of malignancies.…”
Section: Introductionmentioning
confidence: 99%